Packaging of Presto Milkfish in CV. Fania Food Yogyakarta - Pradityo Dwi Giartama; Laksmi Sulmartiwi (Journal of Marine and Coastal Science, 2021)
Milkfish is a commodity that is commonly consumed by the Indonesian people, in addition to its economical price because there are already many choices of milkfish products that have been innovated so that the community's interest in milkfish is increasing. The nutritional content of milkfish is quite high. Field work practices (PKL) are held in Yogyakarta starting from 17 December 2018 to 31 January 2019. At Cv. Fania Food Yogyakarta, on the road to Semanggu KG-1 No.16, Gedong Kuning, Kota Gede, Yogyakarta City, Yogyakarta Special Region. The method used in this field work practice is a descriptive method, namely fact finding with the right interpretation. Descriptive method is a method that addresses the human group of an object, a set of conditions, a system of thought, or a class of events in the present. The scope of packaging criteria includes the process of making presto fish and packaging milkfish presto. Aspects that include packaging criteria ranging from packaging materials, packaging labeling, list of materials used, weight or net contents, name and address of the party producing or entering food into the territory of Indonesia and expiration date, month and year and certification from the relevant agency.